Making friends: active selection of symbionts and rejection of pathogens by the neonatal immune system - Sedney, Colleen J.; Harvill, Eric T. (Frontiers in Immunology, 2023)
The neonatal immune system is generally viewed as deficient compared to adults, often attributed to its incomplete development. This view is reinforced by the extraordinary sensitivity and susceptibility of neonates to certain pathogens. Examination of the basis for this susceptibility has characterized neonatal immunity as skewed strongly toward anti-inflammatory responses, which are interpreted as the lack of full development of the strong inflammatory responses observed in adults. Here we examine the alternative explanation that neonatal immune responses are generally complete in healthy newborns but evolved and adapted to very different functions than adult immunity. Adult immunity is primarily aimed at controlling pathogens that invade the holobiont, with substantial competition and protection conferred by resident microbiota. Rather than simply repelling new invaders, the immediate and critical challenge of the neonatal immune system during the sudden transition from near sterility to microbe-rich world is the assimilation of a complex microbiota to generate a stable and healthy holobiont. This alternative view of the role of the neonatal immune system both explains its strong anti-inflammatory bias and provides a different perspective on its other unique aspects. Here we discuss recent work exploring the initial contact of newborns with microbes and their interactions with neonatal immune responses, contrasting these alternative perspectives. Understanding how the need to rapidly acquire a highly complex and rich microbiota of commensals affects interactions between the neonatal immune system and both commensals and pathogens will allow more targeted and effective collaboration with this system to quickly achieve a more disease-resistant holobiont.